Innovative vacuum distillation technology for preparing refined Al from Al–Mg alloy - Jiafei Yi; Bing He; Jinghui Sun; Peilin Qing; Alin Cao; Xuming Zhang; Lin Chen; Jingyao Xu (Scientific Reports)
Abstract This study presents an advanced approach utilizing vacuum distillation (VD) to purify Al from Al–Mg alloys. The activity coefficients of Al-Mg binary alloy components were meticulously determined by applying the molecular interaction volume model (MIVM), non-random two-liquid (NRTL) model, and Wilson equation. Comparative analysis between experimental data and calculated activity coefficients enabled the selection of an optimal model exhibiting high computational accuracy and extensive applicability. The NRTL model, chosen for its precision, was then employed to compute the activity coefficients of Al-Mg alloy across various temperatures, leading to the development of a vapor-liquid equilibrium (VLE) diagram. This VLE diagram provides a robust quantitative foundation for assessing the purification limits of Al within the temperature range of 973–1373 K in the distillation process. Theoretical analyses underscore that VD offers a rapid and efficient method for Al purification. Experimental verification at a kilogram scale, conducted at 1373 K for 120 min, achieved an Al purity level of 99.9989% with a direct recovery efficiency of 97.98%. Notably, this VD process aligns with environmental standards for sustainable metallurgical practices, as it prevents the release of gaseous emissions or effluents, thereby meeting the industry’s growing demand for eco-friendly Al recycling methods.